Alginate/protamine/silica hybrid capsules with ultrathin membranes for laccase immobilization. Issue 2 (31st May 2012) - Wang, Ji‐Yun; Yu, Hai‐Rong; Xie, Rui; Ju, Xiao‐Jie; Yu, Ya‐Lan; Chu, Liang‐Yin; Zhang, Zhibing
<x xml:space="preserve">Abstract</x> A novel type of core–shell capsules with ultrathin alginate/protamine/silica (APSi) hybrid membranes are successfully fabricated through a coextrusion minifluidic approach and a biosilicification method for immobilization of laccase. The ultrathin membranes were beneficial to the mass transfer across the capsule membranes, and the silica layer on the outer surface was efficient to inhibit the swelling of the capsule membranes. The immobilizing yield was considered to be 100% because all the enzyme molecules were encapsulated inside the capsules through the proposed method, and the laccase activity immobilized in APSi capsules was 61.8 mmol·g–1·min–1. The thermal, pH and storage stabilities of the immobilized laccase in APSi capsules were determined in comparison with free laccase. The stability of encapsulated laccase was significantly improved, which was as high as 67% after 20 days. The residual relative activity of encapsulated laccase remained 45% after 10 cycles. © 2012 American Institute of Chemical Engineers AIChE J, 59: 380–389, 2013